KOMPRESI CITRA DIGITAL ORNAMEN UKIRAN BALI MENGGUNAKAN METODE RLE - I Putu Eka Indrawan Eka; Luh Putu Risma Noviana; Ayu Aprilyana Kusuma Dewi (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2026)
This study investigates the implementation of Run Length Encoding (RLE) for compressing digital images of Balinese carved ornaments as a representation of local cultural heritage. The increasing need for high-resolution digital documentation of cultural artifacts leads to larger file sizes and higher storage and transmission demands. This research adopts an experimental quantitative approach to evaluate compression performance based on compression ratio, file size reduction, and processing time. The results demonstrate that RLE produces compression ratios ranging from 17.04% to 79.08%, depending on the visual complexity and repetitive structure of the ornament patterns. Images with dominant homogeneous areas and repetitive motifs achieved higher compression efficiency, while highly detailed and complex textures resulted in lower ratios. All decompressed images were identical to the original files, confirming that RLE operates as a lossless compression method and preserves visual integrity. The findings highlight the strong relationship between visual structure and algorithmic efficiency, contributing to the integration of information technology in the digital preservation of Balinese cultural artifacts.